A' Ghàidhealtachd and the North American West. Issue 1 (February 2015) - Connell-Szasz, Margaret
Abstract: Sacred land of stories and mythological heroes shaped these indigenous peoples—Gael and Native North American; kinship molded their societies. Resisting colonialism, they shifted the balance of power between Highlands-Lowlands and West-East. Romantic depictions of their regions reshaped other nations' perceptions of Scotland and North America. these regions symbolize the universality among diverse peoples.